Business Clusters and Innovativeness of the EU Economies - Figiel, Szczepan; Kuberska, Dominika (European Scientific Journal, ESJ, 2017)
Business clusters are considered as key drivers shaping competitiveness of local, regional as well as national economies. Supporters of this view argue that business clusters are vehicles to increase productivity, hence development of such economic structures is crucial to assure economic prosperity. One of the more specific reasons pointed out quite recently in the literature is that business clusters stimulate creation and diffusion of innovations. In this paper we test validity of this statement looking at cluster strength and state of cluster development in the EU-28 economies and their innovativeness. The research question we focus on is whether a measurable relationship exists between these two different phenomena. In order to answer this question data on occurrence of business clusters in the EU provided by European Cluster Observatory (ECO) and results of the three types of innovativeness rankings, i.e. Global Innovation Index (GII), Summary Innovation Index (SII), and 12th pillar in the Global Competitiveness Index (GCI), were analyzed. It was found that the level of innovativeness of the EU economies is clearly related to the state of cluster development. This means that innovation and cluster policies should be treated as complementary ones and implemented in a well harmonized manner.